Detecting the US Hegemony in the US Presidents’ Official Speeches: Corpus Analysis of a Selected Donald Trump’s Speeches - DJAOUADI, Hawa; THAMER, Takoua (جامعة الوادي - University of Eloued, 2023)
The United States of America is considered as a global power due to a number of factors that enabled it to take the role of the world leader. For years, America has maintained this role as a global hegemon. Recently, however, there have been many questions, especially during Donald Trump's ascension to the presidential office, whether it is still maintaining this status. This study aims to identify American Hegemony by analyzing Donald Trump's speeches. Following the descriptive-analytical methodology and the qualitative method for corpus analysis, we analyzed six random speeches during Trump's presidential years. The Ant-Conc text analysis program was used as a research tool to identify keywords related to Hegemony, giving the context for each word and its location in the speech. Analysis of the speeches showed that it contains different types of Hegemony: military, economic, scientific, and cultural. Therefore, America still maintains its Hegemony with the prevalence of the economic type. تعتبر الولايات المتحدة الأمريكية قوة عالمية بسبب عدد من العوامل التي مكنتها من القيام بدور القائد والحاكم. حافظت أمريكا لسنوات على هذا الدور كقوة مهيمنة عالمية، لكن في الآونة الأخيرة كان هناك العديد من الأسئلة المثارة ، خاصة أثناء صعود دونالد ترامب إلى منصب الرئاسة ، حول ما إذا لا يزال يحتفظ بهذه المكانة. تهدف هذه الدراسة إلى كشف وتحديد الهيمنة الأمريكية من خلال تحليل خطابات دونالد ترامب. باتباع المنهج الوصفي التحليلي والطريقة النوعية ، قمنا بتحليل ستة خطابات عشوائية خلال سنوات ترامب الرئاسية من خلال استخدام برنامج لتحليل النصوص AntConcكأداة للبحث عن كلمات مفتاحية متعلقة بالهيمنة ، بالإضافة الى أنه يعطي سياق كل كلمة وموقعها في الخطاب. أظهر التحليل أن الخطابات تحتوي على أنواع مختلفة من الهيمنة؛ عسكرية، اقتصادية، علمية، وثقافية. وبالتالي يمكن القول أن أمريكا لا تزال تحافظ على هيمنتها مع وجود غلبة للطابع الاقتصادي
Master Degree in Literature and Civilization
Keywords: Donald Trump’s speeches, Foreign policy, Gramscian Theory Hegemony, The AntConc text analysis program.; امريكا، دونالد ترامب، خطابات دونالد ترامب، الهيمنة، برنامج تحليل النصوص